A Comparison of KL-6 and Clara Cell Protein as Markers for Predicting Bronchopulmonary Dysplasia in Preterm Infants. (27th August 2014) - Wang, Keyi; Huang, Xianmei; Lu, Hui; Zhang, Zhiqun
Abstract : Objectives . To evaluate the predictive characteristics of KL-6 and CC16 for bronchopulmonary dysplasia (BPD) in preterm infants, either independently or in combination. Study Design . This prospective cohort study was performed from 2011 to 2013 with preterm neonates of gestational age ≤32 weeks and birth weight ≤1500 g. Serum KL-6 and CC16 levels were determined 7 and 14 days after birth. Results . Seventy-three preterm infants were studied. BPD was identified in 24 of these infants. After adjusting for potential confounders, serum KL-6 concentrations were found to be elevated in BPD infants at both time points relative to non-BPD infants, while serum CC16 concentrations were lower at 14 days. At both 7 d and 14 d of life the predictive power of KL-6 levels exceeded that of CC16 (area under receiver operating characteristic curve: at 7 d, 0.91 cf. 0.73, P = 0.02 ; at 14 d, 0.95 cf. 0.85, P = 0.05 ). The combination of these markers enhanced the sensitivity further. Conclusions . Serum KL-6 levels higher than 79.26 ng/mL at 14 days postpartum in preterm infants predict the occurrence of BPD. CC16 was less predictive than KL-6 at this time point, but KL-6 and CC16 together enhanced the prediction.